1999
DOI: 10.1021/bi990239w
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Proenkephalin Processing Enzyme Prohormone Thiol Protease (PTP) as a Multicatalytic Cysteine Protease Complex:  Activation by Glutathione Localized to Secretory Vesicles

Abstract: The cysteine protease known as "prohormone thiol protease" (PTP) has been identified as a major proenkephalin processing enzyme in secretory vesicles of adrenal medulla (known as chromaffin granules). This study provides the first demonstration that PTP exists as a multicatalytic cysteine protease complex that can be activated by endogenous glutathione present in chromaffin granules. The high molecular mass nature of PTP, of approximately 185 kDa, was demonstrated by elution of a single peak of 35S-enkephalin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 45 publications
(124 reference statements)
5
50
1
Order By: Relevance
“…In addition, cathepsin L is known to exist as a glycoprotein with glycosylation at Asn-222 (21). Although tryptic peptides containing Asn-222 were not detected in this study, evidence for the glycoprotein nature of the secretory vesicle cathepsin L was suggested by Con A-Sepharose as one of the steps for purification of the PE-cleaving activity (10).…”
Section: Peptide Sequencing By Ms Identifies Cathepsin L As the Cysteinecontrasting
confidence: 55%
See 4 more Smart Citations
“…In addition, cathepsin L is known to exist as a glycoprotein with glycosylation at Asn-222 (21). Although tryptic peptides containing Asn-222 were not detected in this study, evidence for the glycoprotein nature of the secretory vesicle cathepsin L was suggested by Con A-Sepharose as one of the steps for purification of the PE-cleaving activity (10).…”
Section: Peptide Sequencing By Ms Identifies Cathepsin L As the Cysteinecontrasting
confidence: 55%
“…Secretory vesicles were isolated from bovine adrenal medulla by differential sucrose density centrifugation (10) and fixed in 0.2% glutaraldehyde͞2% paraformaldehyde in 0.1 M sodium cacodylate buffer, pH 7.2. Samples were osmicated in 2% osmium tetroxide in 0.1 M cacodylate and embedded in Epon 812.…”
Section: Colocalization Of Cathepsin L With Me In Chromaffin Cells Bymentioning
confidence: 99%
See 3 more Smart Citations